2010
DOI: 10.5152/akd.2010.058
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between severity of coronary artery disease and apolipoprotein E gene polymorphism

Abstract: Relationship between severity of coronary artery disease and apolipoprotein E gene polymorphism Results: The genotype frequencies were 7.5% for E2/E3, 77.4% for E3/E3 and 15.1% for E3/E4. The E2 allele frequency was slightly lower than E4 allele. There were no significant differences between apo E2/E3, E3/E3 and E3/E4 genotypes for severity scorings (26, 41 and 32 respectively, p=0.30) and extent scorings (3.2, 5.5, 4.5, p=0.17). It was found that the most of patients who had E2/3 and E3/4 alleles had low seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The Lebanese population studied here showed similarities to earlier reported ApoE genotypic distributions (high E3 allele frequency and total absence of E2 allele) [ 32 ]. Furthermore, although meta- analyses suggest that apoE4 carriers may have a 40–50% increased CVD risk [ 33 ]; a recent publication showed that 77.4% out of 53 Turkish individuals expressed the apoE3/3 genotype and suggests that the apoE3 is associated with more severe disease than E2 allele [ 34 ]. Finally, the R3500Q mutation of the ApoB gene was not observed in the general Lebanese population and our results are consistent with a previous work [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Lebanese population studied here showed similarities to earlier reported ApoE genotypic distributions (high E3 allele frequency and total absence of E2 allele) [ 32 ]. Furthermore, although meta- analyses suggest that apoE4 carriers may have a 40–50% increased CVD risk [ 33 ]; a recent publication showed that 77.4% out of 53 Turkish individuals expressed the apoE3/3 genotype and suggests that the apoE3 is associated with more severe disease than E2 allele [ 34 ]. Finally, the R3500Q mutation of the ApoB gene was not observed in the general Lebanese population and our results are consistent with a previous work [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glucose was measured by a glucose hexokinase method [ 23 ]. Lipids were analyzed using an enzymatic colorimetric test [ 24 ]. Serum insulin was measured by a two-step sandwich enzyme immunoassay using monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the ratio of TC/HDL-C, the best independent lipid predictor of CHD, is very high in Turkish adults. Low levels of TC, LDL-C and HDL-C are associated with high levels of hepatic lipase, fasting triglycerides and high levels of apolipoprotein-B (20,21,22,23,24). This lipid profile pointing out a genetic disorder constitutes a remarkable early predisposition to CHD.…”
Section: Introductionmentioning
confidence: 99%